Bottom-up approaches to microLEDs emitting red, green and blue light based on GaN nanowires and relaxed InGaN platelets. (1st January 2023) - Bi 毕, Zhaoxia 朝霞; Gustafsson, Anders; Samuelson, Lars
Abstract : Miniaturization of light-emitting diodes (LEDs) with sizes down to a few micrometers has become a hot topic in both academia and industry due to their attractive applications on self-emissive displays for high-definition televisions, augmented/mixed realities and head-up displays, and also on optogenetics, high-speed light communication, etc. The conventional top-down technology uses dry etching to define the LED size, leading to damage to the LED side walls. Since sizes of microLEDs approach the carrier diffusion length, the damaged side walls play an important role, reducing microLED performance significantly from that of large area LEDs. In this paper, we review our efforts on realization of microLEDs by direct bottom-up growth, based on selective area metal–organic vapor phase epitaxy. The individual LEDs based on either GaN nanowires or InGaN platelets are smaller than 1 μm in our approach. Such nano-LEDs can be used as building blocks in arrays to assemble microLEDs with different sizes, avoiding the side wall damage by dry etching encountered for the top-down approach. The technology of InGaN platelets is especially interesting since InGaN quantum wells emitting red, green and blue light can be grown on such platelets with a low-level of strain by changing the indium content in the InGaN platelets. This technology is therefore very attractive for highly efficient microLEDs of three primary colors for displays.